MAKNA BHISAMA KESUCIAN PURA (Kajian dari perspectif Arsitektur) - I Ketut Adhimastra (Jurnal Anala, 2015)
In Balinese society, itâ€™s recently been occurred an emotional debate and dispute of argumentation related to the content of Bhisama Kesucian Pura (temple sacred agreement). An assessment is the realistic distance which emerges as an interpretation to Bhisama Kesucian Pura that will be decreased or narrowed. Itâ€™s Â the critical point thatâ€™s possible to be a further discussion centre item and then, advanced questions Â are : (i) â€œhow many ideal quantitative values for the content of Bhisama Kesucian Pura do we convert?â€, (ii) â€œcould it be 3 (three) Â kilometers, 4 (four) kilometers or more?â€. Thatâ€™s the continued discourse which can be proposed in the hermeneutic study. And the proposed study seems that the result doesnâ€™t contribute the problem solving but it could be to emphasize on the emerging problem analysis. By a few refining on the analysis, itâ€™s proposed to the next study process. Â Analytic scheme of thinking in the study is a deductive nature thatâ€™s Â Â hypothetically-tentatively looking for the logic & ethic meaning on the content of Bhisama Kesucian Pura. Itâ€™s said an hypothetic term because the truth (regarding the content of Bhisama Kesucian Pura) still need indeed to be tested its meaning anymore from the reflective thinking process perspective. Itâ€™s said to be a deductive term because the early study setting comes from the empiric of non assumption but it derives from humanâ€™s thinking or Â intellectual capability to try constructing an abstraction and simplification of an idealism of humanâ€™s world. And itâ€™s said tentative item because the deductive concept is still give a chance to the other value choice that Â reflectively needs to be tested by its meaning anymore